Myeloid-Derived Suppressor Cells: Ductile Targets in Disease - Consonni, Francesca Maria; Porta, Chiara; Marino, Arianna; Pandolfo, Chiara; Mola, Silvia; Bleve, Augusto; Sica, Antonio (Frontiers in Immunology, 2019)
Myeloid-derived suppressor cells (MDSCs) represent a heterogeneous population of immature myeloid cells with major regulatory functions and rising during pathological conditions, including cancer, infections and autoimmune conditions. MDSCs expansion is generally linked to inflammatory processes that emerge in response to stable immunological stress, that alter both magnitude and quality of the myelopoietic output. Inability to reinstate physiological myelopoiesis, would fall in an "emergency state" that perpetually reprogram myeloid cells towards suppressive functions. While differentiation and reprogramming of myeloid cells towards an immunosuppressive phenotype can be considered the result of a multistep process that originates in the bone marrow and culminate in the tumor microenvironment, the identification of its driving events may offer potential therapeutic approaches in different pathologies. Indeed, whereas expansion of MDSCs, in both murine and human tumor bearers, results in reduced immune surveillance and antitumor cytotoxicity, placing an obstacle to the effectiveness of anticancer therapies, adoptive transfer of MDSCs has shown therapeutic benefits in autoimmune disorders. Here, we describe relevant mechanisms of myeloid cells reprogramming leading to generation of suppressive MDSCs and discuss their therapeutic ductility in disease.